2019
DOI: 10.1177/0021998319875209
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analyses of stiffened composite panels with delamination under a compressive load

Abstract: L-shaped stiffened composite panels provide an efficient structure for engineering applications. However, they often produce delamination in the preparation and service process due to a series of factors. To study the effect of different types of delamination on the compressive strength of stiffened composite panels, ABAQUS finite element software was used in combine with the progressive damage subroutine user-defined field variable (USDFLD), and the finite element model was established based on cohesive theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Hence, CFRP structure has been increasingly applied to industries such as airspace. [1][2][3] T-joints are commonly adopted in the design of CFRP structure (Figure 1A), in which the perpendicular part of the stiffener (rib web) divides into two flanges that connect to the skin. Minimum radius is required to maintain the continuity and effective load transmission where the rib web curves into flanges, 4,5 leaving a deltoid cavity at the junction (Figure 1B) that is often filled with CFRP prepreg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, CFRP structure has been increasingly applied to industries such as airspace. [1][2][3] T-joints are commonly adopted in the design of CFRP structure (Figure 1A), in which the perpendicular part of the stiffener (rib web) divides into two flanges that connect to the skin. Minimum radius is required to maintain the continuity and effective load transmission where the rib web curves into flanges, 4,5 leaving a deltoid cavity at the junction (Figure 1B) that is often filled with CFRP prepreg.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber reinforced composites (CFRP) has the capacity of bearing equal force strength with lighter weight compared to metal materials. Hence, CFRP structure has been increasingly applied to industries such as airspace 1–3 . T‐joints are commonly adopted in the design of CFRP structure (Figure 1A), in which the perpendicular part of the stiffener (rib web) divides into two flanges that connect to the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Delamination of the reinforced rib plays a significant role in the strength of the stiffened panel, and subsequent fiber fracture leads to the ultimate failure of the composite stiffened panel. By studying the failure modes of the composite stiffened panels under tensile loads [ 15 ], compressive loads [ 16 , 17 , 18 ], shear loads [ 19 , 20 , 21 ], and with preexisting delamination defects [ 22 , 23 , 24 ], it is possible to use these failure modes to guide process improvements. Furthermore, investigating the effects of different process steps [ 13 ], process parameters [ 25 , 26 ], and fabric ply angles [ 27 , 28 ] on the performance of the composite stiffened panels can provide insights for improving process methods, enhancing molding quality, and optimizing structural design.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of stiffened panels with defects, Ji and Zhao et al 13 studied the debonding behavior with defects, adopted a progressive damage model to predict the expansion of interlaminar damage, and used a bilinear cohesion model to evaluate the debonding damage between skin and stiffener web, and the damage evolution law of this model was in good agreement with the experimental situation. In terms of damage location, Bai et al 14 explored the influence of different damage locations on the bearing capacity and failure mode of the stiffened panels by comparative analysis of the bearing capacity and failure mode of the ribs, skin, and interface bonding layer with elliptical damage under a compression load, as well as the verification of the finite element model. Jasto and Reinoso et al 15 conducted experimental analysis on the initial position and propagation path of T-stiffened panels damage and concluded that the damage started from the triangular position of the T-joint and expanded asymmetrically to both sides, which was consistent with the conclusion drawn by Zhu 16 and Cheng et al 17 .…”
Section: Introductionmentioning
confidence: 99%